Implementation of the Technology Roadmap Methodology to Strengthen Technological Management and Competitiveness in the Tourism Sector of Amazonas, Colombia - Díaz Cobo, Daniel Felipe (2025)
This study presents the implementation of the technology roadmap methodology as a strategic tool to strengthen the competitiveness of the  ourism sector in the Amazonas department of Colombia. In response to local challenges, a roadmap was developed to align technologies with local capacities through a foresight-based planning approach. The main goal was to provide tourism enterprises with strategic tools to help them adapt to market changes and consolidate their position in an increasingly dynamic global environment. Through an intervention involving 50 companies in the sector, a structured methodology was applied, including strategic diagnosis, innovation modeling, and continuous monitoring mechanisms. This initiative made it possible to prioritize digital and sustainable solutions with a high impact on the sector's operations. The results set a precedent for the use of roadmap methodology as an effective tool for enhancing territorial competitiveness.